English criminal system and mental states inference rules - Sánchez Málaga Carrillo, Armando (2018)
Although the discussion about mens rea is still in an incipient state, English criminal law provides a different perspective of analysis, which establishes inference rules of the mental states before defining the conceptual level. The idea that a theory of mental states will only be satisfactory if it allows or makes viable its application in criminal proceedings can constitute a contribution of English jurisprudential development to the dogmatics of continental criminal law.